Exploring Technology Use in English Pronunciation Instruction: A Systematic Review of Trends and Tools - Nursyafida; Reni Eka Putri (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
The integration of technology into education has reshaped pronunciation instruction, introducing innovative tools like Computer-Assisted Pronunciation Training (CAPT) and speech recognition systems. This study aims to systematically review the trends and tools used in technology-assisted pronunciation learning and evaluate their effectiveness. Employing the PRISMA protocol, 27 peer-reviewed studies published between 2006 and 2024 were analyzed through a systematic review method. The findings reveal a significant rise in the use of Computer-Assisted Pronunciation Training (CAPT), mobile applications, and speech analysis software such as Praat, Audacity, and ASR-based systems. These tools offer interactive features, immediate feedback, and personalized learning, contributing to improved phonetic accuracy across segmental and suprasegmental aspects. The majority of studies focused on learners in higher education, ranging from beginner to advanced levels. While results demonstrate the positive impact of technology on pronunciation proficiency, limitations remain in long-term impact evidence and contextual adaptation, particularly in under-resourced settings. This study underscores the potential of digital tools to complement traditional methods and recommends future research to address sustainability, accessibility, and pedagogical integration.